VERIFIKASI FAKTUAL PARPOL DALAM PERSPEKTIF JUSTICE AS FAIRNESS - Hery Wibowo Trisaksono (Refleksi Hukum: Jurnal Ilmu Hukum, 2019)
The legal issue of this paper is whether factual verification of political parties in participating in the 2019 election for all political parties as stated in the Judgment of the Constitutional Court Number 53/PUU-XV/2017 is in accordance with the principle of justice or not. The Constitutional Court Judgment aims to create fairness of the election. Such effort aims to create an electoral justice by the obligation of undertaking the factual verification of political parties held by the General Elections Commission (Komisi Pemilihan Umum). The Constitutional Court laid its constitutional judgment on the interpretation of Article 27 (1) and Article 28D (3) of the 1945 Constitution of the Republic of Indonesia. The use of both Articles interpretation is correct but unfortunately less substantive. In its judgment, the Constitutional Court used legal reasoning based on the ‘equality principle’, whereas the ‘difference principle’ could also be considered in delivering the principle of justice. In conclusion, this paper urges the Constitutional Court to enrich its legal reasoning by applying the difference principle in the theory of justice.